1999
DOI: 10.1046/j.1442-200x.1999.01150.x
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem auditory and visual evoked potentials in children with protein-energy malnutrition

Abstract: The BAEP and fVEP are non-invasive electrophysiologic methods reflecting the integrity or disruption of the central neurologic pathways. The present results confirm the disruption of the central nervous system with the BAEP in children with protein-energy malnutrition, especially in kwashiorkor patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…The kwashiorkor group had significantly longer mean IPL of the waves I-V than the marasmus group on the right ear and than the control group on the left ear. The kwashiorkor group had also significantly longer mean IPL of the waves III-V than the control group on the left [11]. In the study of Bartel et al [12], ABPs were recorded in a group of 22 children with severe malnutrition (kwashiorkor).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The kwashiorkor group had significantly longer mean IPL of the waves I-V than the marasmus group on the right ear and than the control group on the left ear. The kwashiorkor group had also significantly longer mean IPL of the waves III-V than the control group on the left [11]. In the study of Bartel et al [12], ABPs were recorded in a group of 22 children with severe malnutrition (kwashiorkor).…”
Section: Discussionmentioning
confidence: 98%
“…There are limited studies about evaluation of ABPs in children with PEM in the literature, in which all of them showed abnormal ABPs in different degrees in children with malnutrition [9][10][11][12][13]. Durmaz et al [11] studied ABPs in 11 kwashiorkor and 10 marasmus patients and 10 healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have reported alterations in the developing auditory brainstem pathway to various challenges, including malnutrition, nutritional recovery and environmental stimulation (Roncagliolo et al, 1998; Durmaz et al, 1999; Rocinholi et al, 2001a,b). Malnutrition resulted in increases in ABCT, whereas enriched environments reduced conduction times, i.e., promoting faster nervous impulse transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of abnormalities in electroencephalography (EEG) patterns [11,12], auditory brainstem potentials [13,14], auditory [15] and visual [14] evoked potential in children raised on a protein-deficient (PD) diet indicate that consumption of PD diet leads to impairments in neuronal activity and sensory processing.…”
Section: Introductionmentioning
confidence: 99%